Conflito de interesses ambientais: o passado, o presente e o futuro da gestão sustentávelno município de Botucatu (SP) - Ribas, Luiz César [UNESP]; Lemos, Stella Vannucci [UNESP]; Pollo, Ronaldo Alberto [UNESP]; Garcia, Yara Manfrin [UNESP] (My University, 2015)
Entrepreneurs responsible for the housing project “Vale do Sol III”, (claim of deployment), proposed a technique, in order to resolve conflicts of interest arising in respect Vale do Sol I residents (already implemented). Conflicts taken place in accordance with environmental problems that originated (past) in poor drainage of rainwater from Água Fria stream. This work, based on study case method with deductive approach, analyzed the environmental aspects of the area in order to contribute to the process of sustainable management of medium-sized cities (present), as well as analyzing the prospects for adequate outcome environmental demand (future) . In terms of technical and methodological procedures, was used geoprocessing softwares for the purpose of supporting analysis. It was concluded that, technique proposed at Vale do Sol III enterprise, don’t have necessary, sufficient and satisfactory solution in order to, at least, mitigate the problems of area sustainability. In terms of future prospects, it was concluded that, good sustainable environmental management, with preventive measures, from the point of view of mitigating the environmental and urban conflicts, and corrective measures.

Os empreendedores responsáveis pelo projeto habitacional "Condomínio Vale do Sol III" (pretensão de implantação) apresentaram proposta técnica com o intuito de resolver conflitos de interesses gerados com respeito aos moradores do Condomínio Vale do Sol I (já implantado). Os conflitos deram-se em função de problemas ambientais que tiveram origem (passado) na deficiente drenagem das águas pluviais do fundo de vale do córrego Água Fria. Este trabalho, baseado em método de estudo de caso, com abordagem dedutiva, analisou os aspectos ambientais da área, a fim de contribuir para o processo de gestão sustentável de cidades de médio porte (presente), bem como analisar as perspectivas para o adequado desfecho desta demanda ambiental (futuro). Houve, em termos de técnicas e procedimentos metodológicos, a utilização de softwares de geoprocessamento para o fim de suporte à análise técnica. Concluiu-se que a proposta técnica do empreendimento imobiliário Vale do Sol III não se apresenta como solução necessária, suficiente e satisfatória no sentido de, ao menos mitigar, os problemas da sustentabilidade da área. Em termos de perspectivas futuras, concluiu-se que vale a máxima da boa gestão ambiental sustentável, com medidas preventivas, sob o ponto de vista da mitigação dos conflitos ambientais e urbanísticos e medidas corretivas (estruturais).
Environmental interests conflict: the past, the present and the future of the sustainable management at Botucatu municipality (Sao Paulo State - Brazil)
Keywords: Environmental management; Urban management; Water draining mesh; Gestão ambiental; Gestão urbanística; Rede de drenagem pluvial